(untitled) (Филологические заметки, 2019)
My thesis is that, in his drama Boris Godunov, Pushkin did not work solely on the Time of Troubles, but having chosen events that happened around 1600 he opened up the older issues that shaped them. Namely this concerns the polarization that occurred after the Council of Florence (1439). Although this council confirmed cultural plurality and recognized both Latin and Byzantine ritual practices and wordings of the Creed as valid, it was rejected during the reign of Muscovite Grand Duke Basil II, the Blind.